New workplace practices and the gender wage gap: can the new economy be the great equalizer? - Nabanita Datta Gupta; Tor Eriksson (Institute for the Study of Labor (IZA), 2006)
We estimate the effect of introducing new workplace practices on the gender gap in wages in the manufacturing sector. We use a unique 1999 survey on work and compensation practices of Danish private sector firms merged to a large matched employer-employee database. Self-managed teams, project organisation and job rotation schemes are the most widely implemented work practices. Our estimates from a difference-in-differences model of wages and work practices show that the wage gains from adopting new workplace practices accrue mainly to males so that the gender gap in pay increases at the level of the firm, in particular among hourly-paid workers. Considering practices individually, however, a few exceptions are seen: the gender wage gap among salaried workers is significantly reduced in firms which offer project organisation, while the gap in pay among workers paid by the hour is significantly reduced with the use of quality control circles. All in all, however, the new economy is not the great equalizer.
Keywords: J16; J31; M54; 330; new workplace practices; employer-employee data; wage differentials; gender; Lohndifferenzierung; Arbeitsorganisation; Dänemark